Comparison of copolymer emulsions of fluorine and siloxane‐containing acrylates with core–shell structure for water‐repellent cotton fabrics coatings. (18th November 2014) - Lin, J.; Zheng, C.; Zhu, M. N.; Chen, Y. Z.; Lu, P. P.; Liu, Q.; Cai, X. F.; Zhuang, J. W.; Cai, X. M.; Liao, L. P.; Yuan, G. Y.; Xu, C. L.
<x xml:space="preserve">Abstract</x> This paper described the synthesis of copolymer emulsions of fluorine and siloxane‐containing acrylates for water‐repellent cotton fabrics coatings. Chemical composition, morphology structure, and properties of the latex copolymers were investigated by Fourier transform infrared (FTIR), dynamic light scattering (DLS), gel permeation chromatography (GPC), and transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Effects of water‐repellent functional monomers (Rf) on surface morphology, water contact angle, and water‐repellent properties of the coated fabric surface were also studied. The results indicated that Rf greatly influenced molecular mass distribution of the latex copolymers, the molecular aggregation states and orientation of Rf on the coated fabric surface, and water‐repellency of coated cotton fabrics. Copyright © 2014 John Wiley & Sons, Ltd.